Anticancer Activity and Chemical Compounds of Suren Heartwood Extract (Toona sureni) - Rita K Sari; Wasrin Syafii; Suminar A Achmadi; Muhammad Hanafi; Yanotama T Laksana (Masyarakat Peneliti Kayu Indonesia, 2012)
The aims of this research were to determine the yield extracts from continuous extraction of suren heatwood (Toona sureni) in n-hexane, ethyl acetate and methanol solvents, to evaluate this extracts using in vitro anticancer tests (antioxidant, brine shrimp lethality test /BSLT, antiproliferative effects to HeLa servical cancer cell lines, Raji limphoma cancer cell lines, and Vero normal cell lines), and to analyze the best extract based on the anticancer activities. This experiment showed that the yield of methanolic, ethyl acetate, and n-hexane extracts were 0.43%, 0.25%, and 0.18% respectively. The methanolic and ethyl acetate extracts had the high antioxidant activities with EC50 51 and 68 μg ml-1 respectively. Based on BSLT, the ethyl acetate extract was the most active extract (LC50 40 μg ml-1), it followed by the methanolic extract (LC50 116 68 μg ml-1 ), and the n-hexane extract (LC50 161 68 μg ml-1). Further testing showed that the ethyl acetate extract had high antiproliferative effects to Raji (IC50 31 μg ml-1) and HeLa (IC50 65 μg ml-1), but it was more secure against Vero cell lines (IC50 105 μg ml-1). Whereas compounds such as catechol, linalool, and sitosterol contributed to the high anticancer activities of this ethyl acetate extract.Key words: anticancer activity, HeLa cell lines, Raji cell lines, Toona sureni, Vero cell lines